Pipeline Embolization Device for the Treatment of Unruptured Intracranial Dissecting Aneurysms - Chen, Jigang; Tao, Mushun; Han, Jiangli; Feng, Xin; Peng, Fei; Tong, Xin; Niu, Hao; Ma, Ning; Liu, Aihua (Frontiers in Neurology, 2021)
Background: Intracranial dissecting aneurysms (IDAs) are rare but pose significant challenges to treatment. The pipeline embolization device (PED) has been demonstrated to be an effective treatment option with excellent outcomes. Herein, we report our experience with patients treated with the PED for unruptured IDAs. Methods: We retrospectively reviewed our hospital database and identified patients who were treated with PEDs for unruptured IDAs between March 2016 and September 2020. Data including demographics, clinical presentation, aneurysm characteristics, procedural details, intra- or peri-procedural complications, and follow-up details were collected. Results: Eighty patients (61 men, 76.25%) were treated with PED for unruptured IDAs. The most common symptoms were headache (34, 42.5%), dizziness (29, 36.25%), and nausea or vomiting (15, 18.75%). Of these patients, 73 had one aneurysm, and seven harbored two aneurysms. All of them achieved successful PED deployment. Six patients experienced intra- or peri-procedural complications including perforator artery occlusion, thromboembolic, hemorrhagic events, and falling of the stent into the aneurysm sac. Follow-up with digital subtractive angiography was available for 29 patients with a median of 6 months, and 28 (96.56%) patients had aneurysm occlusion. Late thrombosis occurred in four patients, and two of them had unfavorable outcomes. Clinical follow-up showed that a favorable clinical outcome was achieved in 76 (95%) patients, and the mortality rate was 3.75%. Conclusion: Treating unruptured IDAs is safe and effective with long-term favorable clinical and angiographic outcomes. However, the complications of this treatment should be noted. Careful selection of appropriate patients and individualized antiplatelet therapy might be needed.